Determination of The Position and Depth of Aquifers in The Kobakma District of Central Mamberamo District - Duha Awaluddin Kurniatullah; Hery Dualembang; Wika Matana Nion; Helen Gianditha Wayangkau; Rahmat Tatayo Lie (Jurnal Indonesia Sosial Teknologi, 2024)
Groundwater availability in aquifers is crucial for sustaining human settlements, particularly in Kobakma District, Central Mamberamo Regency, where clean water distribution faces significant challenges due to seasonal fluctuations and infrastructure limitations. The lack of groundwater utilization has resulted in local communities relying on rainwater as their primary water source, highlighting the necessity to identify potential groundwater sources. This research aims to determine the position and depth of aquifers in Kobakma District using the geoelectric resistivity method. By identifying subsurface conditions and geological formations, the study seeks to map groundwater availability and provide recommendations for sustainable water resource management in the region. The study employs the geoelectric resistivity method using the Schlumberger configuration to measure subsurface resistivity. Data collection was conducted across 13 test points within Kobakma District. The collected resistivity values were analyzed to interpret subsurface lithology and identify potential aquifer zones. The study primarily focuses on detecting free and confined aquifers, considering variations in rock formations, permeability, and groundwater flow dynamics. The results indicate the presence of two primary aquifer layers: a free aquifer distributed across various locations at depths ranging from 10–60 meters and a confined aquifer found at depths between 100–300 meters. Some test points showed aquifer leakage due to fault structures, influencing groundwater movement. The findings suggest that groundwater sources in the study area are unevenly distributed, requiring site-specific extraction strategies. The study provides an aquifer depth distribution map, offering critical insights for future groundwater management and well-drillin.